2020
DOI: 10.5922/2079-8555-2020-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of cross-border tourist and recreational regions on the Karelian section of the Russian-Finnish border

Abstract: Despite that fact that cross-border tourism and recreation in the Baltic Sea Region have been extensively studied, there are still areas, which require further research. The aim of this article is to identify regions having active cross-border tourism and recreation in the adjacent territories of Finland and the Republic of Karelia. The authors propose to use an indicator characterizing the volume of incoming tourist flows. The number of tourists is not only indicative of the development of cross-border touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Along the Karelian part of the Russian--Finnish border, Manakov et al (2020) identified three cross-border tourism and recreation regions of different development levels: South Karelia, Middle Karelia and North Karelia (Fig. 1).…”
Section: Karelian Borderland As a Research Areamentioning
confidence: 99%
“…Along the Karelian part of the Russian--Finnish border, Manakov et al (2020) identified three cross-border tourism and recreation regions of different development levels: South Karelia, Middle Karelia and North Karelia (Fig. 1).…”
Section: Karelian Borderland As a Research Areamentioning
confidence: 99%
“…1). Today, the Karelian borderlands have several fully developed and emerg ing TTRRs of different levels and orders (for more detail, see [5]). Within the study area, 11 Russian municipalities have been involved in TTRR building.…”
Section: Methodsmentioning
confidence: 99%
“…Finland and Estonia have been among the top ten countries in terms of the outbound tourist flow of Russians for at least the last two decades, which is explained by their proximity to Russia, due to which powerful cross-border tourist flows are formed . Previous studies on the geography of tourism in Finland and Estonia (Chuchenkova, 2019;Manakov et al, 2020; showed that a significant part of tourist flows to these countries is generated in territories adjacent to neighboring countries, where cross-border tourist and recreational regions (CTRR) are formed (Golomidova, 2018;Kropinova, 2016;Manakov and Golomidova, 2018). In addition to tourist and recreational regions forming on the border with Russia, CTRR are being created on the border territories of these countries with other neighbors.…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%
“…This also applies to the border areas of Russia's Northwestern Federal District, in particular, the Republic of Karelia and Pskov Oblast. These two regions are betting on the development of cross-border tourism with neighboring countries, namely, with Finland, Estonia and Latvia, discussed in many publications (e.g., (Manakov et al, 2020;Manakov and Golomidova, 2018;Stepanova, 2014Stepanova, , 2019Stepanova and Shulepov, 2016)).…”
Section: Review Of Earlier Studiesmentioning
confidence: 99%